Gamma knife radiosurgery for Cushing's disease and Nelson's syndrome - Marek, Josef; Ježková, Jana; Hána, Václav; Kršek, Michal; Liščák, Roman; Vladyka, Vilibald; Pecen, Ladislav (Pituitary, 2015)
PURPOSE: This paper presents our 18 years of experience in treating ACTH secreting adenomas (Cushing's disease and Nelson's syndrome) using the Leksell gamma knife (LGK) irradiation. METHODS: Twenty-six patients with Cushing's disease were followed-up after LGK irradiation for 48-216 months (median 78 months). Seventeen patients had undergone previous surgery, in nine patients LGK irradiation was the primary therapy. Furthermore, 14 patients with Nelson's syndrome were followed-up for 30-204 months (median 144 months). RESULTS: LGK treatment resulted in hormonal normalization in 80.7 % of patients with Cushing's disease. Time to normalization was 6-54 months (median 30 months). The volume of the adenoma decreased in 92.3% (in 30.7% disappeared completely). There was no recurrence of the disease. In all 14 patients with Nelson's syndrome ACTH levels decreased (in two patients fully normalized) their ACTH levels. When checked up 5-10 years after irradiation regrowth of the adenoma was only detected in one patient (9.1%), in 27.3% adenoma volume remained unchanged, in 45.4% adenoma volume decreased and in 18.2% adenoma completely disappeared. Hypopituitarism did not develop in any patient where the critical dose to the pituitary and distal infundibulum was respected. CONCLUSION: LGK radiation represents an effective and well-tolerated option for the treatment of patients with Cushing's disease after unsuccessful surgery and may be valuable even as a primary treatment in patients who are not suitable for, or refuse, surgery. In the case of Nelson's syndrome it is possible to impede tumorous growth and control the size of the adenoma in almost all patients.
Keywords: nádorové biomarkery; mladý dospělý; hypersekrece ACTH v hypofýze; Radiosurgery; Biomarkers, Tumor; Humans; lidé; Adenoma; Remission Induction; mladiství; Czech Republic; lidé středního věku; Treatment Outcome; Time Factors; Middle Aged; Nelsonův syndrom; Nelson Syndrome; radiochirurgie; časové faktory; Female; Male; hypofýza; Adult; výsledek terapie; Pituitary ACTH Hypersecretion; Adrenocorticotropic Hormone; mužské pohlaví; adenom hypofýzy vylučující ACTH; Aged; adenom; ženské pohlaví; Pituitary Gland; Young Adult; dospělí; Česká republika; indukce remise; ACTH-Secreting Pituitary Adenoma; adrenokortikotropní hormon; Adolescent; senioři